Using cooperative networks to analyse behaviour in professional Australian Football. Issue 3 (March 2020) - Sheehan, William B.; Tribolet, Rhys; Watsford, Mark L.; Novak, Andrew R.; Rennie, Michael J.; Fransen, Job
Abstract: Objectives: Reducing the dimensionality of commonly reported complex network characteristics obtained from Australian Football League (AFL) games to facilitate their practical use and interpretability. Design: Retrospective longitudinal design where individual players' interactions, determined through the distribution and receipt of kicks and handballs, during official AFL games were collected over three seasons. Methods: A principal component analysis was used to reduce the number of characteristics related to the cooperative network analysis. Results: The principal component analysis derived two individual-based principal components pertaining to in- and out-degree importance and three team-based principal components related to connectedness and in- and out-degree centralisation. Conclusions: This study is the first to provide a simplified, novel method for analysing complex network structures in an Australian Football context with both the team- and individual-derived metrics revealing useful information for coaches and practitioners. This may consequently guide opposition analysis, training implementation, player performance ratings and player selection.